2017
DOI: 10.1038/s41598-017-10827-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of change in high frequency precipitation variability over North America

Abstract: Precipitation variability encompasses attributes associated with the sequencing and duration of events of the full range of magnitudes. However, climate change studies have largely focused on extreme events. Using analyses of long-term weather station data, we show that high frequency events, such as fraction of wet days in a year and average duration of wet and dry periods, are undergoing significant changes across North America. Further, these changes are more prevalent and larger than those associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…; Almeida et al . ; Roque‐Malo & Kumar ). In particular, in Europe a positive trend in the north and a negative one in the south have been observed in the last century (Schonwiese & Rapp ; Fleig et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Almeida et al . ; Roque‐Malo & Kumar ). In particular, in Europe a positive trend in the north and a negative one in the south have been observed in the last century (Schonwiese & Rapp ; Fleig et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, long-term precipitation trends have been observed in several large areas such as southern Europe and the Mediterranean region, central Europe, central North America, central America and Mexico, northeast Brazil, China, Oceania and southern Africa (e.g. Martins et al 2012;Caloiero 2014;Caloiero 2015;Dashtpagerdi et al 2015;Chen et al 2016;Almeida et al 2017;Roque-Malo & Kumar 2017). In particular, in Europe a positive trend in the north and a negative one in the south have been observed in the last century (Schonwiese & Rapp 1997;Fleig et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic greenhouse gas emissions have resulted in increasing global temperatures, enhanced evaporation from soil and the oceans, and higher atmospheric concentrations of H 2 O v , the dominant absorber of infrared radiation (Held and Soden, 2006;Hurley and Galewsky, 2010;Willett et al, 2007). Warmer temperatures and more humid conditions have caused a shift towards less frequent but more intense precipitation events, increasing the risk of both floods and droughts (Roque-Malo and Kumar, 2017;Trenberth, 2011). H 2 O v also modulates production of the dominant atmospheric oxidant, the hydroxyl radical (Thompson, 1992).…”
mentioning
confidence: 99%
“…Roque-Malo and Kumar (2017) investigated the potential microclimate role as an explanatory variable of changes in precipitation indices patterns; they found that the climate diversity or microclimate was responsible for the lack of uniformity in the trends found in their study area. They added that the extent of the uniformity of trends was also influenced by how the changes and rotation in the vegetation covered and land use occurred (Roque-Malo and Kumar, 2017 (INEGI, 1990(INEGI, , 2016. In Aguascalientes, the local microclimate and characteristics of the vegetation at each weather station could be significant contributors in the spatial pattern of extreme index trends.…”
Section: Microclimate Effect In the Spatial Distribution Of Precipimentioning
confidence: 99%